2019
DOI: 10.13057/biodiv/d200605
|View full text |Cite
|
Sign up to set email alerts
|

Searching for potential wood biomass for green energy feedstock: A study in tropical swamp-peat forest of Kutai Kertanegara, Indonesia

Abstract: Abstract. Amirta R, Haqiqi MT, Saparwadi, Septia E, Mujiasih D, Setiawan KA, Sekedang MA, Yuliansyah, Wijaya A, Setiyono B, Suwinarti W. 2019. Searching for potential wood biomass for green energy feedstock: A study in tropical swamp-peat forest of Kutai Kertanegara, Indonesia. Biodiversitas 20: 1516-1523. Recently, much attention has been focused on finding suitable plant species, from different forest ecosystems, having the potential to be used as sources of renewable energy. Most of such information was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It was clearly observed that all woody materials contained C higher than O, indicating its high suitability used as the energy feedstock since high C content will increase the obtained calorific value. Moreover, the C content, with a value of more than 40% in this study, was in line with that of the C content of various tropical woods (Amirta et al 2016;Amirta et al 2019;Yuliansyah et al 2019;Mukhdlor et al 2021). Ratio of H/C was also assessed since a higher value could contribute to improving energy efficiency and decreasing released emissions during combustion (Gopalakrishnan et al 2019).…”
Section: Wood Physicochemical Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…It was clearly observed that all woody materials contained C higher than O, indicating its high suitability used as the energy feedstock since high C content will increase the obtained calorific value. Moreover, the C content, with a value of more than 40% in this study, was in line with that of the C content of various tropical woods (Amirta et al 2016;Amirta et al 2019;Yuliansyah et al 2019;Mukhdlor et al 2021). Ratio of H/C was also assessed since a higher value could contribute to improving energy efficiency and decreasing released emissions during combustion (Gopalakrishnan et al 2019).…”
Section: Wood Physicochemical Propertiessupporting
confidence: 80%
“…Our previous study shows fast-growing species in the lowland community forest, such as Gmelina arborea, Anthocephalus cadamba, Acacia mangium, and Paraserianthes falcataria, had relatively low energy potency (1.37 -1.70 MWh/ton) (Amirta et al 2016). Another study also reported that fastgrowing and shrub species found in the tropical swamppeat forest of Kutai Kartanegara in East Kalimantan generated low energy potency: Kleinhovia hospita (1.76 MWh/ton), Cananga odorata (1.36 MWh/ton), and Octomeles sumatrana (1.17 MWh/ton) (Amirta et al 2019). However, our findings in this study indicated that fast-growing species native to the secondary forest in East Kalimantan, especially F. splendidissima, could produce woody materials with superior energy capacity for electricity production.…”
Section: Wood Quality For Energy Feedstockmentioning
confidence: 96%
“…In the present study, M. pearsonii, M. hypoleuca and M. triloba were classified as species with low wood density (<0.4 g/cm 3 ). The lower wood density is related to fastgrowing ability of plant biomass species, thus affecting the cost of transport, storage and drying process (De Oleivera et al 2013;Amirta et al 2016aAmirta et al , 2016bAmirta et al , 2019.…”
Section: Wood Characteristics Of Plant Speciesmentioning
confidence: 99%
“…Some countries geographically located in the tropical region receive significant benefits to obtain high biomass yield since plants can grow faster than other areas on the earth. Several works have been performed to evaluate some tropical woody species [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%